Impact of the COVID-19 Pandemic on Breast Imaging Education. Issue 3 (9th March 2021) - Chalfant, James S; Pittman, Sarah M; Kothari, Pranay D; Chong, Alice; Grimm, Lars J; Sohlich, Rita E; Leung, Jessica W T; Downey, John R; Cohen, Ethan O; Ojeda-Fournier, Haydee; Hoyt, Anne C; Joe, Bonnie N; et al.
Abstract: Objective: To determine the impact of the COVID-19 pandemic on breast imaging education. Methods: A 22-item survey addressing four themes during the early pandemic (time on service, structured education, clinical training, future plans) was emailed to Society of Breast Imaging members and members-in-training in July 2020. Responses were compared using McNemar's and Mann-Whitney U tests; a general linear model was used for multivariate analysis. Results: Of 136 responses (136/2824, 4.8%), 96 U.S. responses from radiologists with trainees, residents, and fellows were included. Clinical exposure declined during the early pandemic, with almost no medical students on service (66/67, 99%) and fewer clinical days for residents (78/89, 88%) and fellows (48/68, 71%). Conferences shifted to remote live format (57/78, 73%), with some canceled (15/78, 19%). Compared to pre-pandemic, resident diagnostic (75/78, 96% vs 26/78, 33%) ( P < 0.001) and procedural (73/78, 94% vs 21/78, 27%) ( P < 0.001) participation fell, as did fellow diagnostic (60/61, 98% vs 47/61, 77%) ( P = 0.001) and procedural (60/61, 98% vs 43/61, 70%) ( P < 0.001) participation. Most thought that the pandemic negatively influenced resident and fellow screening (64/77, 83% and 43/60, 72%, respectively), diagnostic (66/77, 86% and 37/60, 62%), and procedural (71/77, 92% and 37/61, 61%) education. However, a majority thought that decreased time on service (36/67, 54%) and patient contact (46/79, 58%) would not change residents' pursuit of a breast imaging fellowship. Conclusion: The pandemic has had a largely negative impact on breast imaging education, with reduction in exposure to all aspects of breast imaging. However, this may not affect career decisions.